Plantando Raices en el Nuevo Sur: Mexican-Origin First-Generation College Students' Transformational Impetus in New Destination States. (October 2022) - Ramos, Delma; Camargo, Elsa; Bennett, Cathryn; Kennedy, Brandi
This study examines Mexican-origin first-generation college students' (FGCS) transformational impetus within the sociopolitical context of the Nuevo South. Authors investigate transformational impetus through students' perceptions of knowledge and tools for advocating for equity and social justice in their communities. Results suggest a greater perceived awareness of equity and social justice tools for community uplift among Mexican-origin FGCS than continuing-generation Mexican-origin college students. Implications for research and practice are provided.